PENDIDIKAN ISLAM ALTERNATIF, SEBUAH PENDEKATAN KULTURAL (Analisis atas pemikiran Abdurrahman Wahid) - Asâ€™ari, Kasan; Sholihah, Hidayatus (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2018)
This article is based on the library reseach using an analysis content. This research is trying to analyse an Islamic education based on Abdurrahman wahid or Gus Durâ€™s thought, before he was elected as the fourt President of RI periode, from 1970 to 1998. This essay is based on the text written by Gus Dur, whether in the form of books, articles, newspaper section and any other types of the text , and also the papers from other figures who tried to interprete his thought. Based on Abdurrahman Wahid, the unclear national education direction programmed by the government - since colonial period until the reform era , that did not eliminate the colonial era heritage - is to create "kelas kerani". This class featured an alternative education concept with Paulo Freire and Ivan Illich as the figure with their oppressive education system as the main concept or the domination of strong people to the weak people. Based on Gus dur, the alternative education proposed by Paulo Friere still has the weaknesses in the approach used. It is still political in the confrontative context to the ruler. Therefore, this can make the confrontation against the ruler. This is not appropiate with the Indonesian society character who are not easy to accept the paradigm â€œ the confrontation between â€œthe have and the have notâ€. Thus, Gus Dur offered â€œan alternative educationâ€ with the cultural approachâ€ represented by â€œ Islamic Boarding Schoolâ€.Keywords: National Education, Islamic Education, Islamic Boarding